El trabajo con sentido y el florecimiento humano de los docentes: claves para la calidad en el proceso educativo - Pau Xipell Font; Alfonso Méndiz Noguero (WPOM : Working Papers on Operations Management)
The quality of the educational process is closely tied to teacher performance. In this context, as teachers find meaning in their work and experience human flourishing in their own lives, the quality of their teaching improves. This article explores the relationship between meaningful work and human flourishing among teachers in the Valencian Community (Spain). Specifically, four perceived meanings of work are examined: job, career, calling, and higher calling. Human flourishing is defined through domains such as happiness and life satisfaction, mental and physical health, meaning and purpose, character and virtue, and close social relationships. An analysis of 227 questionnaire responses indicates that teachers who view their work as a calling or a higher calling experience greater flourishing, whereas those who perceive their work merely as a job face greater challenges in achieving it. These findings suggest the need for institutional policies that foster meaningful work among teaching staff, thereby enhancing the overall quality of the educational process.